Trajectories of cough without a cold in early childhood and associations with atopic diseases. Issue 4 (1st December 2022) - Divaret‐Chauveau, Amandine; Mauny, Frederic; Hose, Alexander; Depner, Martin; Dalphin, Marie‐Laure; Kaulek, Vincent; Barnig, Cindy; Schaub, Bianca; Schmausser‐Hechfellner, Elisabeth; Renz, Harald; Riedler, Josef; Pekkanen, Juha; et al.
Abstract: Background: Although children can frequently experience a cough that affects their quality of life, few epidemiological studies have explored cough without a cold during childhood. Objectives: The objective of the study was to describe the latent class trajectories of cough from one to 10 years old and analyse their association with wheezing, atopy and allergic diseases. Methods: Questions about cough, wheeze and allergic diseases were asked at 1, 1.5, 2, 3, 4, 5, 6 and 10 years of age in the European prospective cohort of Protection against Allergy: STUdy in Rural Environment (PASTURE). Specific IgE assays were performed at 10 years of age. Questions regarding a cough without a cold were used to build a latent class model of cough over time. Results: Among the 961 children included in the study, apart from the never/infrequent trajectory (59.9%), eight trajectories of cough without a cold were identified: five grouped acute transient classes (24.1%), moderate transient (6.8%), late persistent (4.8%) and early persistent (4.4%). Compared with the never/infrequent trajectory, the other trajectories were significantly associated with wheezing, asthma and allergic rhinitis. For asthma, the strongest association was with the early persistent trajectory (ORa  = 31.00 [14.03–68.51]), which was inversely associated with farm environment (ORa  = 0.39 [0.19–0.77]) and had a high prevalence of cough triggers and unremitting wheeze. Late and early persistent trajectories were also associated with food allergy. Atopic sensitization was only associated with the late persistent trajectory. Conclusion: Late and early persistent coughs without a cold are positively associated with atopic respiratory diseases and food allergy. Children having recurrent cough without a cold with night cough and triggers would benefit from an asthma and allergy assessment. Growing up on a farm is associated with reduced early persistent cough. Abstract : Five different patterns of cough trajectories during early childhood have been highlighted. Recurrent cough without a cold, with night cough and triggers should lead to allergy and asthma assessment. Growing up on a farm seems to have a protective effect on acute transient cough and early persistent cough.